2020
DOI: 10.3390/resources9040042
|View full text |Cite
|
Sign up to set email alerts
|

Systems Engineering Approach to Slope Stability Monitoring in the Digital Mine

Abstract: Slope stability monitoring in open cut mining is increasingly based on the use of a variety of different sensors and associated analytics, each capable of providing part of the understanding required to manage complex geotechnical environments. Designing an integrated monitoring system that is both attainable and fit for purpose can therefore be particularly challenging. In this paper, a systems engineering approach based on a novel methodology is presented to design the slope monitoring system. The methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…We found that Z. mays had the highest abundance of fruits of the three species studied, which influences that more seeds of this species are removed (Elmouttie, 2009;Kelrick et al, 1986). There is a higher density of squirrels in the corn crops (Flores-Alta et al, 2019), which increases the intensity of seed predation (Gharnit et al, 2020;Minor & Koprowski, 2015).…”
Section: Discussionmentioning
confidence: 79%
“…We found that Z. mays had the highest abundance of fruits of the three species studied, which influences that more seeds of this species are removed (Elmouttie, 2009;Kelrick et al, 1986). There is a higher density of squirrels in the corn crops (Flores-Alta et al, 2019), which increases the intensity of seed predation (Gharnit et al, 2020;Minor & Koprowski, 2015).…”
Section: Discussionmentioning
confidence: 79%
“…The RES approach has been employed for a wide range of geological and engineering topics, including surface blasting, natural slope instability, earthquake‐ and rainfall‐induced slope instability, road cutting slope instability, rockfall hazard assessment, and engineering geological zoning (Hudson & Feng, 2015). Furthermore, recent findings have highlighted the general applicability of RES in geotechnical engineering applications (Rafiee et al., 2019), such as employing fuzzy RES for assessing the rock mass permeability in block mines (Wang et al., 2018), utilizing RES in analysing the liquefaction potential of sandy soils (Ferentinou & Fakir, 2018), investigating rockfall hazards as a primary instability along the Haraz Road in Tehran using remote sensing (Jarahi & Seifilaleh, 2016), and designing a control system for slope stability monitoring in an open‐pit mine using RES and a theoretical process analysis system (Elmouttie & Dean, 2020). RES has also been implemented in various geological settings and scales in Greece.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors can influence animal species' distribution and relative abundance within a given area (Elmouttie, 2009). Large‐scale distribution patterns of species are shaped by environmental and historical constraints (Harcourt & Wood, 2012; Kamilar, 2009; Lehman & Fleagle, 2006).…”
Section: Introductionmentioning
confidence: 99%